COOPERATION OF TOBACCO PRODUCERS" GROUPS AND TOBACCO PROCESSORS OPERATING IN POLAND : A STUDY OF CONTRACTS - Malchar-Michalska, Dominika (Acta Scientiarum Polonorum. Oeconomia, 2013)
The main goal of this paper is to present contractual relations between Polish tobacco producer's groups and their purchasers (contract seasons: 2010/2011, 2011/2012, 2012/2013). The hypothesis of the research is based on the statement: "horizontal (agricultural producers' groups) and vertical (contracts) integration in agriculture lowers farmers' income risk and reduces transaction costs, which strengthens farmers' position in the negotiation process with their purchasers". In verifying the hypothesis, the author conducted empirical research among Polish tobacco producers' groups. The data were collected in the period between January and May 2013. The theoretical background for the research is built on the new institutional economics, contract theory and transaction cost theory. Results provide the supposition that contracts and cooperation within producer's groups lower farmers' income risk, but in the case of contractual arrangements not so significantly. It is caused by following factors: contracts are signed for one season only; they do not fulfill all commitments in contracts and they do not provide financial sanctions, neither for farmers nor for purchasers/first processors. Existing contracts between the tobacco industry and tobacco producers' groups or tobacco growers can be categorised as production contracts in agriculture. Also individual farmer's transaction costs of contracts are lower due to cooperation than tobacco producer's groups. Therefore one can state that quasi-hierarchical structures in the tobacco sector improve efficiency of member's farms.